Curcumin inhibits Akt/mTOR signaling through protein phosphatase-dependent mechanism - Yu, Siwang (2008)
Akt/mTOR signaling plays an important role in tumorigenesis and is dysregulated in many tumors, especially metastatic prostate cancers. Curcumin has been shown to effectively prevent or inhibit prostate cancer in vivo and inhibit Akt/mTOR signaling in vitro, but the mechanism(s) remains unclear. Here we show that curcumin concentration- and time-dependently inhibited the phosphorylation of Akt, mTOR, and their downstream substrates in human prostate cancer PC-3 cells, and this inhibitory effect acts downstream of PI3K and PDK1. Overexpression of constitutively activated Akt or disruption of TSC1-TSC2 complex by siRNA or gene knockout only partially restored curcumin-mediated inhibition of mTOR and downstream signaling, indicating they are not the primary effectors of curcumin-mediated inhibition of Akt/mTOR signaling. Curcumin also activated AMPK and MAP kinases, however, inhibition of these kinases failed to rescue the inhibition by curcumin. Finally, it was demonstrated that the inhibition of Akt/mTOR signaling by curcumin is resulted from calyculin A-sensitive protein phosphatase-dependent dephosphorylation. Our study reveals the profound effects of curcumin on the Akt/mTOR signaling network in PC-3 cells, and provides new mechanisms for the anti-cancer effects of curcumin.